Analysis of wind data for sports performance design: A case study for sailing sports - Pezzoli, A.; Bellasio, R. (Sports, 2014)
Environmental conditions affect outdoor sports performance. This is particularly true in some sports, especially in the sport of sailing, where environmental parameters are extremely influential as they interact directly with strategic analysis of the race area and then with strategic analysis of the performance itself. For these reasons, this research presents an innovative methodology for the strategic analysis of the race course that is based on the integrated assessment of meteorological data measured on the ground, meteorological data measured at sea during the training activities and the results of the CALMET model in hindcasting over a limited scale. The results obtained by the above analysis are then integrated into a graphical representation that provides to coaches and athletes the main strategic directions of the race course in a simple and easy-to-use way. The authors believe that the innovative methodology that has been adopted in the present research may represent a new approach to the integrated analysis of meteorological data on coastal environments. On the other hand, the results of this analysis, if presented with an appropriate technique of meta-communication adapted to the sport sectors, can be used effectively for the improvement of athletes` performances.